2019
DOI: 10.1038/s41598-019-53239-6
|View full text |Cite
|
Sign up to set email alerts
|

The DOT1L inhibitor Pinometostat decreases the host-response against infections: Considerations about its use in human therapy

Abstract: Patients with acute myeloid leukemia frequently present translocations of MLL gene. Rearrangements of MLL protein (MLL-r) in complexes that contain the histone methyltransferase DOT1L are common, which elicit abnormal methylation of lysine 79 of histone H3 at MLL target genes. Phase 1 clinical studies with pinometostat (EPZ-5676), an inhibitor of DOT1L activity, demonstrated the therapeutic potential for targeting DOT1L in MLL-r leukemia patients. We previously reported that down-regulation of DOT1L increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…These results may account for the reduced responsiveness of EPZ-treated cells against viral infection. An increased expression of TRIM25 in uninfected A549 cells EPZ-treated analyzed by highthroughput RNA sequencing, which was confirmed by qPCR, was previously observed [8]. Collectively, the data indicate that the TRIM25 gene is a target for Dot1L histone methylase.…”
Section: Dot1l Inhibition Decreases the Expression Of Trim25 In Influsupporting
confidence: 79%
See 4 more Smart Citations
“…These results may account for the reduced responsiveness of EPZ-treated cells against viral infection. An increased expression of TRIM25 in uninfected A549 cells EPZ-treated analyzed by highthroughput RNA sequencing, which was confirmed by qPCR, was previously observed [8]. Collectively, the data indicate that the TRIM25 gene is a target for Dot1L histone methylase.…”
Section: Dot1l Inhibition Decreases the Expression Of Trim25 In Influsupporting
confidence: 79%
“…Subsequent studies using a chemical inhibitor of Dot1L or specific Dot1L silencers, showed that the downregulation of Dot1L increased influenza virus replication through a decrease of the IFN-β signaling pathway [5]. Conversely, upregulation of Dot1L reduced influenza virus replication [8]. The augmented H3K79 methylation triggered by the influenza virus may increase the IFN-β pathway stimulation and the antiviral response and would represent a host cell defense response to the infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations